2010
DOI: 10.1007/bf03246189
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of vitamin B6 (Pyridoxine) using multi wall carbon nanotube modified carbon-ceramic electrode

Abstract: A simple procedure was developed to prepare a carbon-ceramic electrode (CCE) modified with multi wall carbon nanotube (MWCNT). The electrochemical behavior of pyridoxine was investigated on the obtained electrode in phosphate buffer solution (PBS), pH 7.0. During oxidation of pyridoxine on the MWCNT/CCE, one irreversible anodic peak at E p = 716 mV vs. SCE appeared. Cyclic voltammetric study indicated that the oxidation process is irreversible and diffusion controlled. The number of exchanged electrons in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Addition of acidic or basic solutions affects in a negative way on the analytical method. Both vitB 9 , vitB 12 present in the formulations do not interfere with the assay procedures. …”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of acidic or basic solutions affects in a negative way on the analytical method. Both vitB 9 , vitB 12 present in the formulations do not interfere with the assay procedures. …”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
“…VitB 3 is required for cell respiration, for proper circulation and healthy skin, for the functioning of the nervous system and for the normal secretion of bile and stomach fluids Figure 1: Chemical structures of a) Vitamin B 6 ., b) Vitamin B 3 . [1] Many methods have been developed for the determination of vitB 6 in pharmaceutical formulations include spectrophotometry [2][3][4][5][6], spectrofluorimetry [7], voltammetry [8][9][10][11][12], potentiometry [13,14]. vitB 3 has been determined in pharmaceutical formulations by chemical luminescence [15], spectrophotometry [16].…”
Section: Introductionmentioning
confidence: 99%
“…Three forms of PY are available which are known as, pyridoxal, pyridoxol and pyridoxamine . PY is also necessary for physical and mental growth of the individual . It is reported that vitamin B 6 imposes major effects on gene modulation, sexual behaviour, and immune modulation in HIV‐1 infection .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that vitamin B 6 imposes major effects on gene modulation, sexual behaviour, and immune modulation in HIV‐1 infection . Insufficient concentration level of PY in body leads to illness and various sicknesses such as hypertension, cardiovascular problems, hyperlipidemia, obesity and anaemia . Hence, accurate PY determination is essential in human health diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacopeias describe potentiometric, spectrophotometrics and HPLC method for the determination of PYH and MEH individually from the bulk and tablet dosage form. No reversed-phase high-performance liquid chromatography (RP-HPLC) method is reported in pharmacopeias for the simultaneous estimation of PYH and MEH from their combined formulation, though there are various methods for the determination of PYH and MEH by spectrophotometric [7][8][9][10][11][12], voltammetric [13], HPLC [14][15][16], electrophoresis [17], GLC [18], HPTLC [19], and TLC [20] methods in different pharmaceutical dosages forms. The present work describes the development and validation of stability indicating RP-HPLC method, which can quantify PYH and MEH simultaneously in pharmaceutical solid dosage form.…”
Section: Introductionmentioning
confidence: 99%